Optimizing Empowerment Results: The Important Role of Post-Sewing Training Follow-up at PKBM Anarvani - Salsa Deona; Setiawati Setiawati (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
One of the non-formal education programs is community empowerment, where in this program we can carry out various activities, such as PKBM Anarvani which carries out community empowerment through sewing training. In organizing this program, one of the important points is identification and planning, but there is also a main point that must also be of concern to us, namely the follow-up carried out after the training, which if we pay careful attention to this and carry it out will really help the community. This article discusses this matter, and the research used is descriptive and documents and literature studies. The findings in this article are that the follow-up provided by PKBM Anarvani is to carry out competency tests and regular mentoring and supervision.